2020
DOI: 10.1159/000509937
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Haplogroup Reveals the Genetic Basis of Diabetes Mellitus Type 2 Comorbidity in Psoriasis

Abstract: Objective: Published data show a clear link between psoriasis (Ps) and the increasing prevalence of comorbid conditions, such as diabetes mellitus type 2 (DM2). The role of the mitochondrial genomic haplogroup in the potential coexistence of Ps and DM2 comorbidity is the subject of this study. Material and Methods: Ninety-eight Kuwaiti individuals were recruited in 4 cohorts (20 healthy controls, 15 with DM2, 34 with Ps, and 29 with Ps and diabetes mellitus). An Ion Torrent S5XL was used to sequence mitochondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Herein, our suggestion that haplogroup H may increase risk to Leigh disease is due to the early onset of severe symptoms in our proband according to Hong et al's classification, presented with delayed development under 1 year of age, followed by up to 30 epileptic seizure attacks per day and motor weakness [110]; our prospect is also supported by other literatures which indicated that haplogroup H increases the tendency for other neurodegenerative disorders such as Alzheimer's disease [111,112], Parkinson's disease [113], Huntington's disease [114], amyotrophic lateral sclerosis [115] and multiple sclerosis [116], and is also involved in other non-neurological degenerative disorders such as aortic stenosis [117], diabetes mellitus [118] and osteoarthritis [119,120].…”
Section: Discussionsupporting
confidence: 84%
“…Herein, our suggestion that haplogroup H may increase risk to Leigh disease is due to the early onset of severe symptoms in our proband according to Hong et al's classification, presented with delayed development under 1 year of age, followed by up to 30 epileptic seizure attacks per day and motor weakness [110]; our prospect is also supported by other literatures which indicated that haplogroup H increases the tendency for other neurodegenerative disorders such as Alzheimer's disease [111,112], Parkinson's disease [113], Huntington's disease [114], amyotrophic lateral sclerosis [115] and multiple sclerosis [116], and is also involved in other non-neurological degenerative disorders such as aortic stenosis [117], diabetes mellitus [118] and osteoarthritis [119,120].…”
Section: Discussionsupporting
confidence: 84%
“…Mitochondrial haplogroups are defined by a set of variants in the mitochondrial genome that form specific branches of the mitochondrial phylogenetic tree ( 32 , 33 ). These may be useful as markers of genetic ancestry, population migrations and environmental adaptation, and certain haplogroups have been associated with susceptibility or resistance to specific diseases ( 34 , 35 ). We used the Phy-mer tool that we previously developed ( 33 ) to evaluate the mitochondrial haplogroups and determine haplogroup regions for 18 mothers for which we had lpWGS data ( Figure 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…While few studies have reported on the association of mtDNA haplogroups with FG changes during AHT treatment, some research suggests haplogroups are associated with T2D. 33,36 For instance, Sun and colleagues reported women living with HIV possessing haplogroup L2 (versus non-L2 groups of L0/L3/other) had a 49% lower risk of developing T2D, suggesting haplogroup L2 may potentially be a protective factor. 35 Other reports of haplogroup association with T2D are mostly in other race groups.…”
Section: Discussionmentioning
confidence: 99%